ROLE PLAYING BERBASIS MARKET DAY SEBAGAI INOVASI PEMBELAJARAN IPS MATERI KEGIATAN EKONOMI DI SEKOLAH DASAR - Setya Ratna Dianuri; Septian Eko Rahmanto; Ani Subekti; Triyanto; Supianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores the implementation of Role Playing based on Market Day as an innovative approach to Social Studies (IPS) learning, specifically on economic activities material in elementary school. The problem underlying this research is the low student engagement and limited understanding of abstract economic concepts such as production, distribution, and consumption due to teacher-centered learning and minimal practical activities. The purpose of this study is to describe how Role Playing based on Market Day can create meaningful, contextual, and engaging learning experiences for students. This research employed a qualitative descriptive method. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning activities during the Market Day implementation. The findings show that the Role Playing model integrated with Market Day activities provides authentic learning experiences that help students understand economic activities more concretely. Students actively participated by acting as producers, distributors, and consumers, which enhanced their conceptual understanding, communication skills, collaboration, creativity, and financial literacy. In addition, the learning process became more interactive, enjoyable, and relevant to students’ daily lives. The study concludes that Role Playing based on Market Day is an effective and innovative learning strategy to support meaningful Social Studies learning on economic activities in elementary schools.